Pemikiran Ekonomi Awal: Konsep-Konsep Dasar dan Pengaruhnya Dalam Sejarah Ekonomi - Hasbi, Muhammad; Hidayah, Nurul; Siradjuddin, Siradjuddin (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
The history of conventional economic thought starts from the pre-classical era, with Plato as one of the figures who described the ideal economy in the state. The basic concepts of conventional economics include the theory of wants, free markets, social equality, and political discipline to regulate markets. However, the conventional economic paradigm is different from Islamic economics, which is rooted in the teachings of the Koran and hadith. The great contribution of Muslims in the development of economic thought is often overlooked by Western scholars, who tend to skip important periods in history such as the so-called